Effective Management Style for Resolving Academic and Non-Academic Conflicts in University Colleges in Kathmandu - Chaudhary, Rajeshwer Prasad (Nepal Journal of Multidisciplinary Research, 2023)
This article investigates effective management approaches for resolving academic and non-academic conflicts in education. The objective of the study is to identify and examine strategies that promote successful conflict resolution in educational settings. A quantitative research design was employed, combining quantitative data from educators, administrators, and stakeholders. Findings revealed a range of conflicts, including those related to curriculum, interpersonal relationships, power dynamics, and resource allocation. Various management approaches were identified, such as open communication, mediation and negotiation techniques, feelings building, and the establishment of conflict resolution mechanisms and policies. Participants reported positive outcomes when these approaches were applied, including improved collaboration, enhanced student engagement, and a more harmonious educational environment. The findings provide valuable insights for educational practitioners and administrators seeking to foster productive and inclusive learning environments. By implementing effective management approaches, collaborating can handle conflicts, promote collaboration, and enhance overall educational outcomes. Further research is recommended to explore the long-term effects and sustainability of these conflict resolution strategies.